MAINTAINING HARMONY AMID A BUSY ACTIVITY: FAMILY FUNCTIONS, TRANSFER OF FUNCTIONS, AND THE DUAL ROLES OF CAREER WOMEN - Fuad Hasyim; Yuanita Yuanita; Nisaul Fadillah (Marwah: Jurnal Perempuan, Agama dan Jender, 2026)
Modern social and economic changes have influenced the implementation of the eight family functions, particularly due to the growing number of career women managing dual roles. This study examines how career women working as State Civil Apparatus at the Fakultas Dakwah, UIN Sulthan Thaha Saifuddin Jambi, perform family functions and identifies functional shifts within contemporary families. Using a quantitative descriptive approach, a total sampling (saturated sampling) technique was employed to involve the entire population of 19 career women. Amidst the data collection process, 16 respondents successfully completed the questionnaire, yielding an 84.2% response rate. The findings show that most respondents effectively performed family functions, especially religious, affectional, protective, economic, and environmental functions. However, shifts were identified in the socialization and education functions as well as the religious guidance aspect through the involvement of daycare, domestic helpers, and extended family as an adaptive strategy. Strong family support enabled stability, cooperation, and harmony, demonstrating that career women can sustain family resilience through flexible and collaborative role adjustments.